Making it happen: prevention of mother to child transmission of HIV in rural Malawi - Kasenga, Fyson (CoAction Publishing, 2010)
HIV and AIDS, in resource-limited settings, contribute to increased maternal and infant mortality where such vital indicators are already high. In these settings, babies born to HIV-positive women continue to have added risks of acquiring HIV infection and dying from it before their fifth birthdays if no interventions are employed. Prevention of mother-to-child transmission (PMTCT) is an international initiative whose implications within the local context need to be known. An operational research approach was adopted to study the demand and adherence of key components within the PMTCT Programme among women in rural Malawi. This study was carried out at Malamulo SDA Hospital in rural Malawi and employed the mixture of both quantitative and qualitative approaches. While the introduction of innovative policies in antenatal care (ANC) that has positive impact particularly on marginalised women's access to the services, negative effects are also inevitable. Marginalised women in resource-poor settings fail to deliver at the health facility due to lack of transportation, economic difficulties, gender inequalities, tradition and negative attitude of health workers. Integration of HIV testing and opt-out testing in ANC coupled with the introduction of free maternal care resulted in more women accessing maternal services and PMTCT services. It is as a result of this that institutional delivery facilitates increased adherence to antiretroviral prophylaxis and is supported by both women and the communities. The paper summarises the research conducted and elaborates on how it contributed to actions to improve staff attitude, increase male involvement in reproductive health care and discussions on how available resources can be maximised.